TRAINING ON IMPROVING DIGITAL MARKETING SKILLS FOR THE PROMOTION OF FOOD PRODUCTS OF THE LIBERTI BERINGIN SAKTI FARMER GROUP OF PAGARALAM SELATAN - Ahmad Fali Oklilas; Ali Ibrahim; Ricy Firnando; Yadi Utama (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The training was designed to support the business sustainability of the Liberti Farmer Group located in Beringin Sakti Village, Ulu Rurah Village, Pagaralam Selatan Sub-district, Pagaralam City. The training included training to improve digital marketing skills to promote food products. This activity aims to provide a basic understanding of digital marketing and teach farmer group members how to use digital technology to promote their food products more efficiently and effectively. In this training, they will learn how to use social media as a marketing platform, create engaging content to promote goods, and increase market reach by using online marketplaces and advertisements. The hands-on practice-based method teaches participants how to create digital catalogs, manage social media accounts, and utilize SEO techniques to increase the visibility of their products. The training can improve the skills of farmer group members in utilizing digital technology for promotion, expanding the market for agricultural products, and increasing income.